2015
DOI: 10.1016/j.apgeog.2015.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Geographically-weighted regression analysis of percentage of late-stage prostate cancer diagnosis in Florida

Abstract: This study assessed spatial context and the local impacts of putative factors on the proportion of prostate cancer diagnosed at late-stages in Florida during the period 2001–2007. A logistic regression was performed aspatially and by geographically-weighted regression (GWR) at the nodes of a 5 km spacing grid overlaid over Florida and using all the cancer cases within a radius of 125 km of each node. Variables associated significantly with high percentages of late-stage prostate cancer included having comorbid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…This presentation of the GWLR results maintains comparability with previous GWR-based research on environmental inequality outcomes [70]. This new visualization strategy also contributes to a growing literature that uses FDR-correction techniques in the presentation of GWLR results [58,61,65].…”
Section: Statistical Techniquessupporting
confidence: 60%
See 2 more Smart Citations
“…This presentation of the GWLR results maintains comparability with previous GWR-based research on environmental inequality outcomes [70]. This new visualization strategy also contributes to a growing literature that uses FDR-correction techniques in the presentation of GWLR results [58,61,65].…”
Section: Statistical Techniquessupporting
confidence: 60%
“…Since the introduction of geographically weighted regression (GWR) techniques [54,55], studies have used GWR to model spatial non-stationarity in a wide variety of multivariate statistical relationships. These include applications of geographically weighted logistic regression (GWLR) to model local variation in the predictors of binary outcomes spanning multiple subfields in human and physical geography [56][57][58][59][60][61][62][63][64][65][66][67][68]. Within the environmental inequality outcomes literature, spatial non-stationarity has been identified in the aggregate-level population vulnerability predictors of industrial air-toxic releases in New Jersey, USA [69], estimated lifetime cancer risk from cumulative ambient air-toxic pollution in Florida, USA [70], and vegetation land cover in shrinking and growing US cities [71].…”
Section: Hypothesis 5 (H5)mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has indicated that health outcomes always present spatial autocorrelation at fine geographical scale (Chalkias et al 2013;Goovaerts et al 2015). In this context, the traditional OLS (ordinary least square regression) should be limited in identifying the local influential factors, since the homoscedasticity assumption of OLS is not satisfied (LeSage and Pace 2009).…”
Section: Spatial Regressionmentioning
confidence: 99%
“…The routinely recorded statistical data make it possible to establish an ADI at a fine geographical resolution. In addition, a typical characteristic of health outcome at the fine geographical sale is the spatial autocorrelation in local concentrations (Chalkias et al 2013;Goovaerts et al 2015). Several studies have demonstrated the role of spatial autocorrelation in explaining the geography of cancer prevalence associated with environmental pollution (Eitan et al 2010;Muir et al 2004;Sundmacher and Busse 2011).…”
Section: Introductionmentioning
confidence: 98%